Effect of Combined Low Dose Human Gonadotropic Hormone, Follicle Stimulating Hormone, and Testosterone Therapy (LFT Regimen) Versus Conventional High Dose Human Gonadotropic Hormone and Follicle Stimulating Hormone on Spermatogenesis and Biomarkers in Men With Hypogonadotropic Hypogonadism - Singhania, Nikhil; Devi, Konsam Biona; Kaur, Japleen; Bhansali, Anil; Gorsi, Ujjwal; Sachdeva, Naresh; Arora, Sunil; Rai, Ashutosh; Walia, Rama (Endocrine practice, 2024)
In male congenital hypogonadotropic hypogonadism (CHH), it was observed that lower dose human gonadotropic hormone (hCG) can maintain normal intratesticular testosterone levels. We propose this study to compare the low-dose hCG, follicle stimulating hormone (FSH), and Testosterone (T) [LFT Regimen] to conventional treatment to induce virilization and fertility. This open-label randomized pilot study was conducted from June 2020 to December 2021. CHH were randomly assigned to either the LFT regimen (Group A)-low-dose hCG (500U thrice per week), FSH (150U thrice per week), and T(100 mg biweekly) or conventional therapy(GroupB) with high hCG dose(2000U thrice per week) and the same FSH dose. The hCG dosage was titrated to reduce anti-mullerian hormone (AMH) by 50% and normalization of plasma T in groups A and B, respectively. The primary objective was to compare the percentage of individuals who achieved spermatogenesis between the two groups. Out of 30 patients, 23 (76·7%) subjects achieved spermatogenesis, and the median time was 12 (9-14·9) months. There was no difference in achieving spermatogenesis between the two groups (64·3% vs 7·5%,P = 0·204), and even the median time for spermatogenesis was similar (15months vs 12months,P = 0·248). Both groups had nonsignificant median plasma AMH at spermatogenesis, [6·6 ng/ml (3·3-9·76) vs4·41 ng/ml (2·3-6·47), P = 0·298]. Similarly, the median plasma Inhibin B at spermatogenesis between groups were comparable [152·4 pg/ml (101·7-198·0) vs49·1 pg/ml (128·7-237·3), P = 0·488]. A reasonable approach to induce fertility in male CHH is to initiate combination therapy using FSH, low-dose hCG targeting AMH <6·9 ng/ml, along with T to achieve normal range. Monitoring AMH could serve as a proxy indicator of spermatogenesis.